2006
DOI: 10.1248/bpb.29.1613
|View full text |Cite
|
Sign up to set email alerts
|

MCI-186 (3-Methyl-1-phenyl-2-pyrazolin-5-one) Attenuated Simulated Ischemia/Reperfusion Injury in Cultured Rat Hippocampal Cells

Abstract: The reactive oxygen species and Ca 2؉ overload play a critical role in ischemia/reperfusion (I/R) injury. MCI-186 has potent effects in the brain as a free radical scavenger in ischemia-reperfusion. Acute glucose-oxygen deprivation and subsequent reoxygenation were used to model ischemia/reperfusion injury in cultured hippocampal cells. MCI-186 reduced malondialdehyde level and raised the SOD activity when applied upon reoxygenation in a dose-dependent manner compared with the untreated group. The peak neuropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
(20 reference statements)
1
21
0
Order By: Relevance
“…More importantly, in the present study, the reduction in the a-and b-wave amplitudes caused by I/R was significantly improved in animals treated with edaravone. A previous study showed that edaravone could decrease calcium overloading, increase mitochondrial potential, and reduce neuronal apoptosis through inhibiting lipid peroxidation in the rat hippocampal I/R model [15] . Wen et al reported that edaravone could relieve oxidative stress through inhibiting the JNK-c-Jun pathway in the senile rat cerebral I/R model and therefore protect cerebral neurons [14] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…More importantly, in the present study, the reduction in the a-and b-wave amplitudes caused by I/R was significantly improved in animals treated with edaravone. A previous study showed that edaravone could decrease calcium overloading, increase mitochondrial potential, and reduce neuronal apoptosis through inhibiting lipid peroxidation in the rat hippocampal I/R model [15] . Wen et al reported that edaravone could relieve oxidative stress through inhibiting the JNK-c-Jun pathway in the senile rat cerebral I/R model and therefore protect cerebral neurons [14] .…”
Section: Discussionmentioning
confidence: 96%
“…Others have reported that edaravone has antioxidative effects and reduces apoptosis [13,14] . In vitro and in vivo studies have also shown that edaravone could effectively inhibit I/R-induced apoptosis [15,16] . Edaravone was also suggested to have neuroprotective effects on transient forebrain or focal ischemia in rodent models [17,18] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was reported that apoptosis was mainly induced by oxygen-glucose deprivation [33,34]. In addition, one study showed that the percentage of apoptotic cells induced by oxygen-glucose deprivation was signifi cantly inhibited by edaravone [14]. These fi ndings suggest that ROS production may be one of the key factors that determine neuronal viability in both the necrotic pathway induced by glutamate neurotoxicity and the apoptotic pathway induced by oxygen-glucose deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the mechanisms of the protective effect involve inhibition of the activation of microglia [10,11] and astrocytes [10], and protection against endothelial cell injury [12], as well as the inhibition of cerebral edema [13]. Regarding the effect on the neurons themselves, it has been reported that cultured hippocampal neurons and neuronal PC 12 cells treated with edaravone were protected against glucose-oxygen deprivation [14,15]. However, as far as we know, there have been no reports about the effect of edaravone on neurons themselves against glutamate neurotoxicity, i. e., excitotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities ] i overload, have been linked to neuronal apoptosis induced by ischemia-reperfusion [21] . The increasing [Ca 2+ ] i leads to the activation of many pivotal cellular processes that can alter the cellular functions and even lead to cell injury and death, including neuronal apoptosis [22,23] .…”
Section: Effects Of Resveratrol On [Camentioning
confidence: 99%